1991
DOI: 10.1136/adc.66.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Effect on intelligence of relaxing the low phenylalanine diet in phenylketonuria.

Abstract: A total of 599 children with phenyketonuria, who had been treated early, were followed up prospectively in order to examine the association between intellectual progress from 4 to 14 years of age and control of phenylalanine concentrations. The phenylalanine rose from around 400 imol/l during the first four years to above 900 ,mol/l by 12 years. The Subjects and methods SUBJECTSThe subjects in the study were followed up prospectively by the staff of the Phenylketonuria Register using the protocol described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 12 publications
3
44
0
2
Order By: Relevance
“…Many reports have shown that optimum outcome occurs when dietary therapy is started early and continued indefinitely. 22,[25][26][27][28][29][30][31][32][33][34][35][36] As with other chronic illnesses, decreased compliance and poor dietary control increase with age, especially after 6 years of age. 17,25,37,38 Older individuals who have discontinued dietary therapy are at risk for developing loss of intelligence, magnetic resonance imaging findings consistent with white matter dysfunction, and occasionally acute demyelinating neuropathies.…”
mentioning
confidence: 99%
“…Many reports have shown that optimum outcome occurs when dietary therapy is started early and continued indefinitely. 22,[25][26][27][28][29][30][31][32][33][34][35][36] As with other chronic illnesses, decreased compliance and poor dietary control increase with age, especially after 6 years of age. 17,25,37,38 Older individuals who have discontinued dietary therapy are at risk for developing loss of intelligence, magnetic resonance imaging findings consistent with white matter dysfunction, and occasionally acute demyelinating neuropathies.…”
mentioning
confidence: 99%
“…However, even in patients who are well controlled during childhood, neurological deterioration has been observed (Villasana et al, 1989;Thompson et al, 1990;Cleary et al, 1994;Weglage et al, 1995) and children with PKU have, on average, an IQ score that is 0.5 s.d. less than the general population (Smith et al, 1991). The reason for this may be the effects of raised phe on brain myelination but the relative deficiency of DHA supply may also contribute to a poorer intellectual outcome (Cockburn et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, para prevenir el retardo mental a largo plazo, es necesario realizar el seguimiento médico, nutricional, bioquímico, neurológico y psicológico perió-dicos y permanentes 15,16 .…”
Section: Discussionunclassified
“…Iniciar el tratamiento precozmente y mantener el nivel de FA en sangre bajo 10 mg/dl (600 µmol/ l) permite un desarrollo mental normal [15][16][17] . Los resultados de este estudio, demuestran que a los 4 y 6 meses de edad, 13 de los 16 pacientes evaluados (81%) tenían MDI y PDI normal.…”
Section: N V E S T I G a C I ó Nunclassified